Promoting young people's mental health and well-being through participation in the arts: A mixed-methods service evaluation of the Zinc Arts ArtZone programme. (1st June 2017) - Wilson, Ceri; Sharpe, Darren
Arts-for-health initiatives are associated with improvements in mental health, wellbeing and social inclusion; however, research amongst young people is sparse. The aim of the study was to conduct a mixed-methods evaluation of a participatory arts programme for young people with, or at risk of, mental ill health. The Zinc Arts ArtZone programme involved working with individuals aged 11–25 in south-east England, engaging them in arts activities over ten-week courses in community and secure unit settings. 122 course participants completed pre/post measures of mental illness severity and well-being, and 34 participants took part in interviews and focus groups. Mental illness severity significantly decreased and mental well-being significantly increased. Participants reported social and emotional benefits including decreased social isolation and increased social inclusion and mental well-being. Participatory arts interventions may serve as a useful tool in tackling increasing mental ill health amongst young people.